Anaerobic fermentation slurry from kitchen waste as carbon source for wastewater treatment - CHE Dongni; ZHANG Liqiang; ZHANG Minghui; LIU Yongxia; LI Ning (Gongye shui chuli)
This work took the kitchen wastes from Liuta Mining Area of Shendong Coal as example, to investigate the effects of hydrogen peroxide(H2O2) pretreatment on the performance of kitchen waste and the production efficiency of volatile fatty acid(VFAs) from anaerobic fermentation. Then the nitrogen and phosphorus removal effect of wastewater treatment with anaerobic fermentation slurry from kitchen waste as carbon source were investigated. Results indicated that the H2O2 pretreatment could promote the release of dissolved organic matters in kitchen wastes and enhance the fluidity of kitchen waste slurry. As a result, the VFAs production after H2O2 pretreatment increased from 10 810-18 131 mg/L to 21 000-28 000 mg/L, while the dominant fermentation products were converted from butyric acid to acetic acid. These suggested that the H2O2 pretreatment achieved a significant improvement in the production efficiency of VFAs. Furthermore, when the anaerobic fermentation slurry from pre-treated kitchen waste as carbon source of wastewater treatment plants, the concentration of NH4+-N and TP in the effluent was less than 1 mg/L and 0.5 mg/L, which was equivalent to the treatment effect when glucose was used as the carbon source. All these demonstrated that the kitchen waste in the mining area had good usability.